2015
DOI: 10.1140/epjc/s10052-015-3257-4
|View full text |Cite
|
Sign up to set email alerts
|

Eddington–Born–Infeld cosmology: a cosmographic approach, a tale of doomsdays and the fate of bound structures

Abstract: The Eddington-inspired-Born-Infeld scenario (EiBI) can prevent the big bang singularity for a matter content whose equation of state is constant and positive. In a recent paper [Bouhmadi-Lopez et al. (Eur. Phys. J. C 74:2802, 2014] we showed that, on the contrary, it is impossible to smooth a big rip in the EiBI setup. In fact the situations are still different for other singularities. In this paper we show that a big freeze singularity in GR can in some cases be smoothed to a sudden or a type IV singularity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 98 publications
(261 reference statements)
0
56
0
Order By: Relevance
“…These two behaviours can be visualised nicely by plotting the scale factor normalised by the scale a B as a function of time, which can be seen in figure 25. A more detailed analysis of these cosmological solutions was further investigated in [323,111,79,80,78].…”
Section: Eddington-inspired Born-infeld Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…These two behaviours can be visualised nicely by plotting the scale factor normalised by the scale a B as a function of time, which can be seen in figure 25. A more detailed analysis of these cosmological solutions was further investigated in [323,111,79,80,78].…”
Section: Eddington-inspired Born-infeld Gravitymentioning
confidence: 99%
“…The other polynomial whose cosmology has also been investigated is the first one, that was called Minimal model. The corresponding action is given by 80) where the constants have been chosen as to match GR without a cosmological constant in the low curvature regime. A possible cosmological constant term will be considered as part of the matter sector.…”
Section: Elementary Symmetric Polynomials Extension: Minimal Modelmentioning
confidence: 99%
“…One of the most interesting features is that EiBI is equivalent to GR in the vacuum while it introduces modifications in dense matter environments, where GR is experimentally not well probed. EiBI is able to describe, with only a single extra parameter (κ), astrophysical objects such as the Sun [19] and the internal structure of compact objects [20][21][22][23][24][25][26], and the cosmological expansion of the Universe [22,[27][28][29][30][31] (for comprehensive reviews see [7,12] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The EiBI theory has been shown to be able to remove the big bang singularity for a radiation-dominated universe through a loitering effect or a bounce in the past [26]. The ability of the theory to smooth other cosmological singularities in a phantom-dominated universe has also been studied in [35][36][37][38]. Unfortunately, it was found that even though the EiBI theory can lead to the avoidance of the big bang and the alleviation of some smoother singularities, the BR singularity is still unavoidable.…”
Section: Introductionmentioning
confidence: 99%